Using Exoplanets to Determine Photospheric Properties of Fast-Rotating A-type Stars - Lam,Madeline (2024)
Exoplanets and their host stars are intrinsically related as they form from the same accretion disc, and are therefore expected to have similar chemical composition. Thus, knowing the composition of exoplanet host stars is important for developing planetary formation and migration theories. There has been a recent uptick in studies of ultra-hot Jupiter atmospheres as their orbital configurations provide an ideal test-bed for transmission spectroscopy, enabling detections of many chemical species. However, this class of exoplanets tend to orbit fast-rotating A-type stars with severely rotation broadened spectra. Line blending in rotation broadened spectra hinders the accurate measurement of photospheric parameters and chemical abundances in the stellar photosphere. We bypass this problem of rotation broadened spectra by introducing a new method of isolating the non-broadened stellar spectrum using the effect of a transiting exoplanet. During an exoplanet transit, the planet obscures part of the light emitted from the star. The spectrum of this light is characteristic of the stellar disc at the planet's location and is less affected by rotation broadening. This allows us to resolve weaker absorption lines and hence more precisely measure chemical abundances in fast-rotating exoplanet host stars. This will ultimately allow ultra-hot Jupiter systems to be better characterised in terms of their evolutionary mechanisms. With the obscured stellar spectrum from behind the transiting exoplanet, $F_{\text{obsc}}$, at every time-series observation, we reconstruct the disc-integrated non-broadened stellar spectrum, which we term the isolated spectrum, $F_{\star,N}$. This method is tested with a proof-of-concept using synthetically generated spectra and then applied to real observations from HARPS. We focus on the WASP-189 system which consists of the ultra-hot Jupiter WASP-189 b transiting across its fast-rotating A-type host star. We then apply standard spectral fitting procedures to the isolated spectrum, $F_{\star,N}$, to obtain best-fit global photospheric parameters ($T_{\text{eff}}$, $\log g$ and [Fe/H]) and individual chemical abundances. We have proven that we can obtain photospheric parameters with significantly improved accuracy compared with the broadened stellar spectrum. This method is not limited to ultra-hot Jupiter systems, but can be also be applied to other transiting systems in which abundance determinations via spectral synthesis are imprecise due to severe line blending.
Keywords: planets and satellites: gaseous planets; stars: abundances; stars: individual: WASP-189; stars: planetary systems; techniques: spectroscopic